Racial Disparities in Health Status: A comparison of the morbidity among American Indian and U.S. adults with diabetes - O'Connell, Joan (American Diabetes Association, 2010)
OBJECTIVE: American Indians and Alaska Natives are 2.3 times more likely to have diabetes than are individuals in the U.S. general population. The objective of this study was to compare morbidity among American Indian and U.S. adults with diabetes. RESEARCH DESIGN AND METHODS: We extracted demographic and health service utilization data for an adult American Indian population aged 18–64 years (n = 30,121) served by the Phoenix Service Unit from the Indian Health Service clinical reporting system. Similar data for a U.S. population (n = 1,500,002) with commercial health insurance, matched by age and sex to the American Indian population, were drawn from the MartketScan Research Database. We used Diagnostic Cost Groups to identify medical conditions for which each individual was treated and to assign a risk score to quantify his or her morbidity burden. We compared the prevalence of comorbidities and morbidity burden of American Indian and U.S. adults with diabetes. RESULTS: American Indians with diabetes had significantly higher rates of hypertension, cerebrovascular disease, renal failure, lower-extremity amputations, and liver disease than commercially insured U.S. adults with diabetes (P < 0.05). The American Indian prevalence rates were 61.2, 6.9, 3.9, 1.8, and 7.1%, respectively. The morbidity burden among the American Indian with diabetes exceeded that of the insured U.S. adults with diabetes by 50%. CONCLUSIONS: The morbidity burden associated with diabetes among American Indians seen at the Phoenix Service Unit far exceeded that of commercially insured U.S. adults. These findings point to the urgency of enhancing diabetes prevention and treatment services for American Indians/Alaska Natives to reduce diabetes-related disparities.